2013
DOI: 10.1089/fpd.2012.1306
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Plasmid Replicons Encoding theblaCMY-2Gene in Broad-Spectrum Cephalosporin-ResistantEscherichia colifrom Livestock Animals in Japan

Abstract: Broad-spectrum cephalosporin (BSC) resistance has increased in Escherichia coli isolates from broiler chickens in Japan since 2004. The purpose of this study was to understand the epidemiology of BSC-resistant E. coli in livestock animals. Among 3274 E. coli isolates from 1767 feces of apparently healthy animals on 1767 farms between 2004 and 2009, 118 ceftiofur (CTF)-resistant isolates (CTF MIC ≥4 μg/mL) were identified on 74 farms. After elimination of apparently clonal isolates from a single animal, 75 sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 28 publications
4
37
0
1
Order By: Relevance
“…Among wild animals, bla CMY-2 has been reported to be mainly associated with IncI1 plasmids in E. coli from Dutch wild birds and wild seagulls in the US (Poirel et al, 2012; Veldman et al, 2013). Other plasmid types, such as IncB/O, IncK, and IncF, have also been identified as carriers of bla CMY-2 in wildlife (Poirel et al, 2012; Veldman et al, 2013), as previously reported in humans, companion animals, broiler chickens, and retail meat (Bortolaia et al, 2014; Hansen et al, 2016; Hiki et al, 2013; So et al, 2012; Vogt et al 2014). Thus far, the IncA/C plasmid, a major carrier of bla CMY-2 , has not yet been identified in wild animals.…”
Section: Plasmid-mediated Ampc β-Lactamase-producing Enterobacteriacesupporting
confidence: 63%
“…Among wild animals, bla CMY-2 has been reported to be mainly associated with IncI1 plasmids in E. coli from Dutch wild birds and wild seagulls in the US (Poirel et al, 2012; Veldman et al, 2013). Other plasmid types, such as IncB/O, IncK, and IncF, have also been identified as carriers of bla CMY-2 in wildlife (Poirel et al, 2012; Veldman et al, 2013), as previously reported in humans, companion animals, broiler chickens, and retail meat (Bortolaia et al, 2014; Hansen et al, 2016; Hiki et al, 2013; So et al, 2012; Vogt et al 2014). Thus far, the IncA/C plasmid, a major carrier of bla CMY-2 , has not yet been identified in wild animals.…”
Section: Plasmid-mediated Ampc β-Lactamase-producing Enterobacteriacesupporting
confidence: 63%
“…Ceftiofur, a veterinary third-generation cephalosporin, is used commonly to treat infectious diseases in dairy cattle (12). Resistance to ceftiofur is correlated with clinically relevant drug resistance in human medicine (13) and has been used as a phenotypic marker for targeted research of third-generation cephalosporin resistance genes in bovine bacterial flora (14)(15)(16). The E. coli isolates used in the retrospective study were obtained during previous studies using various selection methods focused primarily on ceftiofur resistance.…”
Section: Methodsmentioning
confidence: 99%
“…Fresh fecal samples were collected from two or three healthy broilers at the different farms in each prefecture as previously described [14]. E. coli was isolated from the fecal samples using desoxycholate–hydrogen sulfate–lactose agar (Eiken Co., Ltd., Japan).…”
Section: Methodsmentioning
confidence: 99%